Manipulating and controlling for personality effects on visualization tasks. (July 2015) - Ottley, Alvitta; Crouser, R Jordan; Ziemkiewicz, Caroline; Chang, Remco
Researchers in human–computer interaction and visualization have recently been challenged to develop a better understanding of users' underlying cognitive processes in order to improve system design and evaluation. While existing studies lay a critical foundation for understanding the role of cognitive processes and individual differences in visualization, concretizing the intuition that each user experiences a visual interface through an individual cognitive lens is only half the battle. In this article, we investigate the impact of manipulating users' personality on observed behavior when using a visualization. In a targeted study, we demonstrate that personality priming can result in changes in behavior when interacting with visualizations. We then discuss how this and similar techniques could be used to control for personality effects when designing and evaluating visualizations systems.